Healthy lifestyle scales to assess general and clinical population: A systematic review with narrative synthesis - Elaheh Dehghani; Keyvan Karimi; Hananeh Ghelichi‐Moghaddam Sokke; Mohammad Amin Khadembashiri; Fatemeh Ghavidel; Amir Hossein Memari (Wiley, 2024)
Abstract Background Adopting a healthy lifestyle and improvements in medical care have led to an increase in life expectancy. Thus, the development and implementation of techniques for assessing healthy lifestyles have garnered more attention recently. Finding and evaluating healthy lifestyle assessment tools across all demographics is the goal of this systematic review. Method Using online databases PubMed, Scopus, Web of Science, and APA PsycINFO, a systematic literature review was carried out in accordance with Preferred Reporting Items for Systematic Review and Meta‐analyses. Registration DOI https://doi.org/10.17605/OSF.IO/ZD9XK for the review has been set on Open Science Framework (OSF). Using the quality standards proposed for measuring features of health status surveys, two independent reviewers evaluated the methodological quality ratings of the eligible studies. Results From 7480 studies, 47 eligible instruments were identified and included in the review. Most of the studies followed the World Health Organization's definition of healthy lifestyle to develop the scales. The instruments are categorized into those used to assess general lifestyle or healthy lifestyle in general as well as in the clinical population. Physical activity, nutrition, tobacco use, alcohol use, and stress management were the most assessed modules of healthy lifestyle. Furthermore, validity, reliability, responsiveness, floor and ceiling effects, and interpretability were among the psychometric qualities that were frequently assessed. Conclusion Lifestyle questionnaires can be used to identify specific risk factors in a variety of populations, as well as to plan community‐based intervention programs, by acting as a predictive diagnostic tool and preventive measure. The majority of the assessments of healthy lifestyles that are currently accessible require improvements.